Implementasi Program Sekolah Adiwiyata (Studi Pada Smp Negeri 6 Bantan Kecamatan Bantan Kabupaten Bengkalis) - Nashari Nashari (STAIN Bengkalis, 2017)
Implementation of Adiwiyata School Program (Study at SMP Negeri 6 Bantan District Bantan Bengkalis Regency) This research was conducted on the basis of SMP Negeri 6 Bantan Bantan District Bengkalis become Adiwiyata school. Researcher use qualitative method with descriptive approach. This study shows that the school passed the selection at the district level and succeeded in becoming the Adiwiyata School at Riau Province Level. Result of research indicate that there are four program that is applied that is komposter; garden development; breeding and waste management programs. The program is implemented based on components such as environmentally sound policies; implementation of an environment-based curriculum; participatory environmental activities and management of environmentally friendly means of support. Implementation of the program there are internal support factors that are qualified human resources and the vision, mission, functions and management of a good budget. The external supporting factors of the guardian side and the provision and cost of school operations sourced from the local government of Bengkalis Regency and the cooperation between the principal, teachers, administrative staff and learners are so compact.